Pelatihan Dan Pendampingan Digital Marketing Sebagai Strategi Pemasaran UMKM Di Kelurahan Semolowaru - Annisa Kurniawan; Loisa Eunike Lude; Muhammad Tapus Revaldo; Roziana Febrianita (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
Product marketing through social media and e-commerce is one of the most effective ways to expand market reach in this digital age. In fact, in this era of increasingly sophisticated technology, it opens up great opportunities for Micro, Small and Medium Enterprises (MSMEs) actors to be able to market their products outside the city, to abroad. However, there are many MSMEs who do not understand how to use social media and e-commerce to increase their sales. This happened to several MSMEs in RW XI Semolowaru Indah II, where they had quality products but did not understand modern ways to market these products. By looking at this case, the author held digital marketing training and assistance for MSMEs at RW XW Semolowaru Indah II. This method is done in two ways, namely: 1) Digital marketing training by bringing in resource persons. 2) Door to door digital marketing assistance. The result of this training and mentoring is that MSMEs actors already have a personal Instagram, and also some want to register for e-commerce, and they also understand how to market products through social media.